Cosmology and Satire: Symbolic Transformation in Javanese Wayang and Ottoman Karagöz - Akhmad Mughzi Abdillah; Nirwan Nirwan; Berrin Sarıtunç (Universitas Cokroaminoto Palopo, 2026)
This article examines Wayang and Karagöz as two shadow theatre traditions that have long functioned as vehicles of cultural meaning, moral instruction, and social commentary. Although both forms are widely recognized in their respective cultural contexts, they are often studied separately, leaving limited comparative insight into how performance organizes cosmology, ethics, and public life across different traditions. The central question of this study is how Wayang and Karagöz transform inherited narrative materials into locally meaningful performative systems, and what this comparison reveals about the relationship between tradition, satire, and identity. To address this problem, the article uses comparative textual analysis of existing scholarly literature on both traditions. Previous studies have shown that Wayang localizes Indian epic materials within Javanese cosmology and ethics, while Karagöz develops within Ottoman urban culture as a form of satire and social critique. Building on this research, the article argues that Wayang emphasizes harmony, ritual order, and moral refinement through figures such as Semar and the punakawan, whereas Karagöz stages social plurality through the Karagöz–Hacıvat relationship and comic mediation. The findings suggest that both traditions function not only as entertainment but also as culturally authoritative media for teaching, social critique, and communal reflection. The article further shows that their modern significance lies in their adaptation to national identity projects, with Wayang becoming associated with Indonesian cultural heritage and Karagöz with Turkish cultural memory.